Estimating sustainable timber production from tropical forests - Vanclay, J.K. (1996)
Natural forests in the humid tropics differ from temperate and plantation forests in several ways: there may be many tree species; many of these may occur infrequently; there may be a large range of tree sizes and shapes present; tree ages may be unknown and indeterminate; and despite the luxuriant appearance some rainforests, growth rates may be relatively low. This has many implications for timber harvesting and yield estimation and means that most of the estimation techniques devised for even-aged single-species forests cannot be used. A timber harvest represents the culmination of many years of growth, even in "fast growing" plantations. Thus, unlike the farmer of annual crops, the forest manager must consider the distribution of the harvest over time. Several "rules-of-thumb" for estimating the annual allowable cut are examined, with special emphasis given to the selection of the cutting cycle, to growth and harvesting models, and to inventory and monitoring systems. Strengths and weaknesses of cutting cycle analysis are discussed, and are contrasted with the more sophisticated yield scheduling systems. Tools, techniques and information sources for estimating timber yields are reviewed. Yield calculations should make full use of existing information, including data from old surveys and casual inspections. Remote sensing and geographic information systems offer several interesting possibilities for yield estimation, particularly for sensitivity testing, but are not without limitations. A check list and extensive references are given.